2020
DOI: 10.21203/rs.3.rs-41584/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medical status of patients presenting for treatment at an Australian dental institute: A cross-sectional study

Abstract: Background: Individuals seeking dental treatment often present with medical conditions which may affect dental treatment provision. The purpose of this study was to determine the prevalence of medical conditions and medication use among individuals attending dental clinics at a Western Australian tertiary institution.Methods: This observational study examined the general demographics, medical and social histories of 873 subjects presenting for a general dental examination at a Western Australian Tertiary Insti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Similar prevalence estimates (38%) were reported by Aggarwal et al in a study of dental patients in a teaching dental institute in India [4]. A recent study by Frydrych et al identified medical problems in 86% of dental patients in Australia, and the most common medical problems included cardiovascular disease, allergy, and mental disorders [11]. On the other hand, Oyetola et al reported the occurrence of medical conditions in 11.7% of patients in Nigeria [10].…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Similar prevalence estimates (38%) were reported by Aggarwal et al in a study of dental patients in a teaching dental institute in India [4]. A recent study by Frydrych et al identified medical problems in 86% of dental patients in Australia, and the most common medical problems included cardiovascular disease, allergy, and mental disorders [11]. On the other hand, Oyetola et al reported the occurrence of medical conditions in 11.7% of patients in Nigeria [10].…”
Section: Introductionsupporting
confidence: 69%
“…International literature indicates variations in the prevalence estimates of medical conditions in dental patients in different countries [4,[7][8][9][16][17][18]. e prevalence of medical conditions in dental patients was 11.7% in Nigeria [10], 12.2% in ailand [20], 27.7% in Ireland [21], 38% in India [4], 42% in West Indies [9], 52.5% in the U.S. [22], and 86% in Australia [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antihypertensives, bronchodilators, antidepressants and proton‐pump inhibitors were the most commonly prescribed medications in both 2011 and 2020. A recent study 7 assessing patients at an Australian dental institute reported antidepressants being the medications most commonly used in patients presenting for treatment.…”
Section: Discussionmentioning
confidence: 99%